A Comprehensive Case Report of Relapsing-Remitting Multiple Sclerosis (RRMS) in a 40-Year-Old Female Patient - Jagadesh, Jagadesh; Nallaperumal, Sharath; Padma, V.; Varma, Chaitanya; M, Ishaivaanan (Journal of Neonatal Surgery, 2025)
Neuroinflammation, demyelination, and axonal degeneration are hallmarks of multiple sclerosis (MS), a persistent inflammatory disease of the CNS. A thorough description of a 40-year-old female patient suffering from RRMS is provided in this case report. Clinical manifestations, diagnostic evaluations, management strategies, and disease progression are explored. The report aims to provide insight into the complexity of MS management and the challenges in tailoring treatment to individual patient needs